2021
DOI: 10.1155/2021/9985972
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning for Joint Channel/Subframe Selection of LTE in the Unlicensed Spectrum

Abstract: In recent years, to cope with the rapid growth in mobile data traffic, increasing the capacity of cellular networks is receiving more and more attention. To this end, offloading the current LTE-advanced or 5G system’s data traffic from licensed spectrum to the unlicensed spectrum that is used by WiFi systems, i.e., LTE-Licensed-Assisted-Access (LTE-LAA), has been extensively investigated. In the current LTE-LAA system, a Listen-Before-Talk (LBT) approach is implemented, which requires the LTE user also perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…• adjust the TXOP duration of coexisting Wi-Fi and LTE-LAA systems based on buffered downlink data in APs and evolved Node Bs (eNBs) [216], and • select optimal channel and subframe numbers [236].…”
Section: A Fair Channel Sharing With Cellular Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…• adjust the TXOP duration of coexisting Wi-Fi and LTE-LAA systems based on buffered downlink data in APs and evolved Node Bs (eNBs) [216], and • select optimal channel and subframe numbers [236].…”
Section: A Fair Channel Sharing With Cellular Networkmentioning
confidence: 99%
“…This approach not only improves performance in terms of LTE's rates but also in terms of reducing disturbances in Wi-Fi's performance and achieving coexistence fairness with Wi-Fi networks and other LTE-LAA operators. Finally, Kishimoto et al [236], use Q-learning for joint channel/subframe selection. Only LTE-LAA BSs perform learning and start with zero knowledge of neighboring Wi-Fi systems.…”
Section: A Fair Channel Sharing With Cellular Networkmentioning
confidence: 99%
“…Centralized collection of data regarding LTE-LAA and WiFi systems by the LTE cloud wireless access network (C-RAN) is proposed to support MMEs. Other papers implement distributed Q-learning to: (i) optimize spectral efficiency of WiFi/LTE-LAA coexistence [196], (ii) scale CW parameters depending on the collision probability observed in each backoff stage by LTE user entitys (UEs), as opposed to the legacy hybrid automatic repeat request (HARQ) mechanism implemented in cellular networks [200], (iii) select optimal TXOP and muting periods (i.e., giving opportunities for WiFi transmissions) which outperform random and round-robin mechanisms [190], (iv) adjust the TXOP duration of coexisting WiFi and LTE-LAA systems based on buffered downlink data in APs and evolved Node Bs (eNBs) [184], and (v) select optimal channel and subframe numbers [204]. In [184], both WiFi and LTE-LAA nodes serve as agents, which take actions (select TXOPs from 4, 6, 8 and 10 ms) and calculate rewards based on the target occupancy ratio.…”
Section: A Fair Channel Sharing With Cellular Networkmentioning
confidence: 99%
“…It is shown that this approach not only improves performance in terms of LTE rate but also in terms of reducing disturbances in WiFi's performance and achieving coexistence fairness with WiFi networks and other LTE-LAA operators. Finally, in [204], Q-learning is used for joint channel/sub-frame selection. In this work, only LTE-LAA BSs perform learning with zero knowledge of concurrent WiFi systems.…”
Section: A Fair Channel Sharing With Cellular Networkmentioning
confidence: 99%